2019
DOI: 10.3389/fpsyg.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

She Always Steps in the Same River: Similarity Among Long-Term Partners in Their Demographic, Physical, and Personality Characteristics

Abstract: In mate choice, individuals consider a wide pool of potential partners. It has been found that people have certain preferences, but intraindividual stability of mate choice over time remains little explored. We tested individual consistency of mate choice with respect to a number of demographic, physical, and personality characteristics. Only mothers were recruited for this study, because we wanted to find out not only whether women choose long-term partners with certain characteristics but also whether the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
1
11
1
Order By: Relevance
“…In summary, our findings indicate that although children associate beardedness with traits related to dominance and mate choice, these associations show distinct developmental patterns and develop throughout childhood. We also confirm past research that beards operate primarily as a badge of status and maturity rather than as an attractive ornament, enhancing judgements of masculinity, age, dominance and aggressiveness that secondarily influence women's mate preferences (Dixson et al, 2017b(Dixson et al, , 2019b potentially as long-term and paternally investing partners (Dixson et al, 2019a, Neave & Shields, 2008Štěrbová, Tureček, & Kleisner, 2019).…”
supporting
confidence: 88%
“…In summary, our findings indicate that although children associate beardedness with traits related to dominance and mate choice, these associations show distinct developmental patterns and develop throughout childhood. We also confirm past research that beards operate primarily as a badge of status and maturity rather than as an attractive ornament, enhancing judgements of masculinity, age, dominance and aggressiveness that secondarily influence women's mate preferences (Dixson et al, 2017b(Dixson et al, , 2019b potentially as long-term and paternally investing partners (Dixson et al, 2019a, Neave & Shields, 2008Štěrbová, Tureček, & Kleisner, 2019).…”
supporting
confidence: 88%
“…Although the idea that there is both shared consensus and unique idiosyncrasy in what people want in a romantic partner is not new (7), our data show stability in distinctive partner personality through actual relationship formation and, importantly, using 2 different partners' own self-reports. This allows us to bypass retrospective biases that may be present in describing past partners (13). Further, our data suggest that the stability in partner personality evidenced in our data was something more than people meeting someone similar to themselves.…”
Section: Discussionmentioning
confidence: 59%
“…12). As such, relying on one person's self-reports, as in previous research (13), may not be a reliable way to get information about their partner. Rather, direct assessments of different partners people have actually dated and assessments from multiple sources (particularly the partners themselves) are required to adequately address the question of partner consistency.…”
Section: Stability In Partnering Patternsmentioning
confidence: 91%
“…Despite the success of evolutionary psychological approaches in understanding human mating, it is perhaps time to significantly broaden the scope of understanding beyond honest signalling approaches to different viewpoints, such as imprinting [124] or Fisherian runaway [125]. Recent evidence has indicated that mate choice decisions are consistent, that people seem to have a "type" of partner they prefer [126,127], and that optimising their preferred traits are what drives attractiveness perceptions. Focusing more closely on these approaches allows for a systematic exploration of the theoretical space of psychological and morphological traits of possible partners.…”
Section: Discussionmentioning
confidence: 99%